Effect of Organically Modified Layered Silicate on Degradation of Chloroprene Rubber - Hyok Lee, Jin; Woo Bae, Jong; Soo Kim, Jung; Seok Choi, Yoo; Ju Jo, Nam (Asian Journal of Chemistry, 2013)
This study examined the effect of organically modified layered silicate on the degradation of chloroprene rubber with particular focus on the nano-size and structure of organically modified layered silicate, as well as the tortuous structure of the resulting nanocomposites. Chloroprene rubber/organically modified layered silicate nanocomposites were prepared using the melt intercalation method. X-ray diffraction revealed the dispersion of organically modified layered silicate. Compared to pure organically modified layered silicate, the basal space of chloroprene rubber/organically modified layered silicate nanocomposite was shifted from 2.1 nm to 4.2 nm and the XRD peak was shifted from 3.96º to 2.35º 2q. XRD confirmed that organically modified layered silicate layers were intercalated into the chloroprene rubber matrix. Compared to the conventional filler loaded composites, the chloroprene rubber/organically modified layered silicate nanocomposite exhibited high mechanical properties. The chloroprene rubber/organically modified layered silicate nanocomposite showed 28, 43 and 43 % improvement in tensile strength, tear strength and compression set, respectively, compared to the no filler-loaded chloroprene rubber composite. The change in the mechanical properties after the thermal aging test was dependent on the aspect ratio and dispersion state of the filler. Organically modified layered silicate was dispersed on the nano-level. The chloroprene rubber/organically modified layered silicate nanocomposite showed the lowest change in mechanical properties. In the modulus profile, chloroprene rubber-organically modified layered silicate showed a smaller deviation of the modulus according to the position and a lower 10 % compressive modulus than chloroprene rubber-NF. Intercalation of the organically modified layered silicate layers to the chloroprene rubber matrix led to the formation of a tortuous structure. The tortuous structure hindered oxygen diffusion and decreased the degradation rate. An analysis of the oxygen permeability confirmed that the chloroprene rubber/organically modified layered silicate nanocomposite had formed a tortuous structure.